Localization of individual mullaway (Argyrosomus japonicus) within a spawning aggregation and their behaviour throughout a diel spawning period - Parsons, Miles; McCauley, Robert; Mackie, Michael; Siwabessy, Paulus; Duncan, Alexander (Oxford University Press 2009, 2009)
Mulloway (Argyrosomus japonicus) are a soniferous member of the Sciaenidae. During summer in the Swan River of Western Australia, individuals form spawning aggregations in turbid waters around high tide, during late afternoon and early evening. Mulloway produce pulsed vocalizations that are characteristic of the species and to an extent of individuals. Crepuscular passive acoustic recordings of vocalizing mulloway were collected from a four-hydrophone array during March 2008. Arrival-time differences proved the most robust technique for localization. Corroboration of fish position was observed in relative energy levels of calls, surface-reflected path differences, and relative range of successive calls by individuals. Discrete vocal characteristics of the tone-burst frequency and sound-pressure levels assisted the determination of caller identification. Calibration signals were located within a mean distance of 3.4 m. Three-dimensional locations, together with error estimates, were produced for 213 calls during a sample 4-min period in which 495 calls were audible. Examples are given of the movement and related errors for several fish successfully tracked from their vocalizations. Localization confirmed variations in calling rates by individuals, calling altitudes, and the propensity to vary call structure significantly over short periods, hitherto unreported in this species.